Enhancing Functional Compounds in Sesame Oil through Acid-Soaking and Microwave-Heating of Sesame Seeds - Jitkunya Yuenyong; Suchintana Limkoey; Chonlathit Phuksuk; Thitima Winan; Chonlada Bennett; Sudarat Jiamyangyuen; Sugunya Mahatheeranont; Phumon Sookwong (Foods)
This study investigated whether pre-treating sesame (Sesamum indicum L.) seeds with a combination of acid-soaking and microwave-heating could significantly enhance the quality of the resulting sesame oil, particularly by increasing its content of functional compounds such as lignans, tocopherol, phytosterol, and squalene. The study revealed that soaking the sesame seeds in a solution of HCl and citric acid, along with microwave-heating, significantly increased the content of these compounds. The detected ranges were sesamin (1365–6927 µg g−1), sesamolin (605–3493 µg g−1), tocopherol (69.31–282.76 µg g−1), asarinin (ND–383.52 µg g−1), sesamol (ND–49.59 µg g−1), phytosterol (3690–6201 µg g−1), and squalene (532−1628 µg g−1). Additionally, the study found that the pre-treatment of sesame seeds had a minimal effect on the fatty acid composition, antioxidant activity (92.94–95.08% DPPH scavenging activity), and oxidative stability (2.13–2.90 mg MDA kg−1 oil). This is the first study to demonstrate that using acid-soaking and microwave-heating to prepare sesame seeds can produce sesame oil enriched with functional compounds, potentially benefiting cosmetic, pharmaceutical, and health applications.